A case of disseminated superficial porokeratosis associated with giant porokeratosis in pregnancy - Biju Vasudevan; Manas Chatterjee; Rajan Grewal; Vandana Rana; Nikita Lodha (Wolters Kluwer Medknow Publications, 2014)
A 23-year-old pregnant lady presented with dark raised lesions over face, axillae, and upper limbs of 15-day duration. She was 35 weeks pregnant at the time of onset of the lesions. Dermatological examination revealed hyperpigmented plaques on the face and papules with raised borders in the axillae and proximal arms. Skin biopsy from both the lesions revealed a diagnosis of porokeratosis. She was treated with emollients alone and the lesions regressed four weeks following delivery. This case is being reported for the rare occurrence of the combination of disseminated superficial porokeratosis with giant porokeratosis in pregnancy.